Gender Differences in Imaginary Audience And Depressive Symptomatology Among College Students - Kalsoom, Ume; Rahim, Sabeen; Akbar, Huma (Journal of Gandhara Medical and Dental Science, 2020)
OBJECTIVES: The present study aimed to investigate gender differences on Imaginary Audience (IA) and depression among college students. METHODOLOGY: Six hundred college students, both boys (n=299) and girls (n=274) completed cross sectional survey. Data was collected from different colleges of Peshawar (KPK) from September- December 2016 using purposive sampling technique. The age range of the sample was 17-22 (M=19, SD=1.47) years. Two scales, New Imaginary Audience Scale (NIAS) and Beck Depression Inventory (BDI) were administered to them. RESULTS: Analysis of the findings was made using stepwise deletion technique for sample distribution and t-test. Statistically significant gender differences were found on New Imaginary Audience Scale (t=-2.48, p= .001) and Beck Depression Inventory (t=3.07, p= .02). Mean score was on NIAS were among girls, while on depression boys mean scores were prominent. CONCLUSION: The results of the present study concluded gender differences on both variables i-e NIAS and Depression. The findings further suggest that girls have prominent features of new imaginary audience in their student’s life whereas, boys pertain depressive symptoms during this period.